P037: The Ontario Emergency Department Return Visit Quality Program: a provincial initiative to promote continuous quality improvement. (15th May 2017) - Chartier, L.B.; Ostrow, O.; Yuen, I.; Kutty, S.; Davis, B.; Hayes, E.; Davidek, M.; Lau, C.; Vigo, A.; Yang, F.; Fairclough, L.; Ovens, H.J.
Abstract : Introduction: Analyzing the charts of patients who have a return visit to an emergency department (ED) requiring hospital admission (termed 'RV') is an efficient way to identify adverse events (AEs). Investigating these AEs can inform efforts to improve the quality of care provided. The ED RV Quality Program (RVQP) is a new initiative supported by Ontario's Ministry of Health and Long-Term Care and managed by Health Quality Ontario. It aims to promote a culture of continuous quality improvement through routine audit/investigation of RVs.Methods: The provincial program is mandatory for high-volume EDs and requires auditing of some 72-hour RVs and all 7-day RVs involving 'sentinel diagnoses' (subarachnoid hemorrhage [SAH], acute myocardial infarction [AMI], or pediatric sepsis [PS]). A standardized audit template is followed that includes assessment of the type/severity and underlying causes of AEs, and potential actions for improvement.Results: 73 high-volume EDs and 16 smaller EDs (collectively receiving 90% of all ED visits in Ontario) are participating in the program. Nine months' data have been released to date, comprising 33, 956 RVs (1.05% of 3, 235, 751 ED visits). Of these, 233 RVs (0.69%) were for a sentinel diagnosis (SAH=11, AMI=191, PS=31). The most common presenting complaint on the index visit was abdominal pain (18%). The most common discharge diagnosis following RV admission was acute appendicitis (3.8%).Conclusion: The ED RVQP aims to improve the quality of care provided in Ontario's EDs by requiring hospitals to conduct audits of RVs and plan actions for improvement when quality gaps are identified. Participating hospitals have completed hundreds of audits to date.